The checkpoint protein Zw10 connects CAL1-dependent CENP-A centromeric loading and mitosis duration in Drosophila cells - Pauleau, Anne-Laure; Bergner, Andrea; Kajtez, Janko; Erhardt, Sylvia (PLoS Genetics, 2019)
A defining feature of centromeres is the presence of the histone H3 variant CENP-A that replaces H3 in a subset of centromeric nucleosomes. In Drosophila cultured cells CENP-A deposition at centromeres takes place during the metaphase stage of the cell cycle and strictly depends on the presence of its specific chaperone CAL1. How CENP-A loading is restricted to mitosis is unknown. We found that overexpression of CAL1 is associated with increased CENP-A levels at centromeres and uncouples CENP-A loading from mitosis. Moreover, CENP-A levels inversely correlate with mitosis duration suggesting crosstalk of CENP-A loading with the regulatory machinery of mitosis. Mitosis length is influenced by the spindle assembly checkpoint (SAC), and we found that CAL1 interacts with the SAC protein and RZZ complex component Zw10 and thus constitutes the anchor for the recruitment of RZZ. Therefore, CAL1 controls CENP-A incorporation at centromeres both quantitatively and temporally, connecting it to the SAC to ensure mitotic fidelity.